Arts and crafts of ancient Greece - Morris, Ting.; Young, Emma (London : Franklin Watts, 2007)
Describes the art and architecture of ancient Greece along with simple instructions for making a Greek mural and scroll, an amphora, and an actor's mask.
Includes index.
7.0
3-6
3-6
Keywords: Clothing and dress -- History -- Juvenile literature; Handicraft -- Greece -- History -- Juvenile literature; Clothing and dress -- History; Handicraft -- History; Clothing and dress -- History; Handicraft -- History; Greece -- Civilization -- Juvenile literature; Greece -- Civilization; Greece -- Civilization